Influence of long-term operation on the properties of main gas pipeline steels. A review - Nyrkova, L.I.; Osadchuk, S.O.; Goncharenko, L.V.; Rybakov, A.O.; Kharchenko, Yu. O. (Physics and Chemistry of Solid State, 2024)
Underground pipelines during operation are affected by mechanical and corrosive factors. The susceptibility of cathodically protected pipe to hydrogen degradation increases, which contributes to stress-corrosion cracking. It is believed that the main factor in pipeline steels degradation is deformation aging, which increases strength and reduces plasticity. Volume microdamages also develop in long-time exploited steels. But in many cases, the base metal and welded joints of long-term operated pipelines retain satisfactory performance. Due to the high value of viscosity and plasticity of the metal in an as-received state, the metal state of long-term operated gas pipelines can be considered satisfactory.